»The walls ought to be demolished from the inside«: KRUM and the failure of the prison struggle in Sweden in the 1960s and 70s - Nilsson, Roddy (Nordisk Tidsskrift for Kriminalvidenskab, 2019)
Abstract Swedish Artikeln behandlar fångkampen i de svenska fängelserna vid 1960-talets slut och 1970-talets början. Framför allt diskuteras den roll Riksförbundet för Kriminalvårdens humanisering (KRUM) spelade. Delvis i motsättning till den tidigare forskningens uppfattningen att fångarnas relativa nederlag kan förklaras av en kombination av en svag förhandlingsposition, otillräcklig förhandlingskompetens, motpartens överlägsna resurser och taktiska skicklighet och vikande stöd från media, argumenterar artikeln för att nederlaget också måste förstås i relation till brister i fångarnas strategi och till otillräckligheten i den maktmodell, med betoning framför allt på abstrakta rättigheter, som fanns inom KRUM. På den sistnämnda punkten kolliderade KRUM:s liberalt dominerade modell tydligt med den syn på fången som vuxit fram inom den svenska kriminalvården under decennierna efter andra världskriget. Abstract English The article deals with a struggle for inmates’ rights in Swedish prisons at the end of the 1960s and the beginning of the 1970s. The focus is on the role played by the Swedish National Association for the Humanization of Prisons (KRUM). Previous research has argued that the inmates ultimately lost their struggle due to a combination of their weaker bargaining position, their lack of negotiation skills, their counterpart’s superior tactical skill and resources, and declining support for their cause in the media. The current article contends that the defeat must also be understood in relation to deficiencies in the prisoners’ strategy and to the inadequacy of the power model, with its emphasis on abstract rights, which existed within KRUM. On the latter point, KRUM’s liberal-dominated model clearly clashed with the view of the prisoner that has emerged within the Swedish Correctional Service since World War II.